PROBLEMATIC ISSUES IN TEACHING ENGLISH TO B1 LEVEL STUDENTS USING AUDIO-VISUAL AUTHENTIC MATERIALS - Ungboeva , Dildora Bakhrom qizi; Erdonova , Muattar Rahmonovna (Educational Research in Universal Sciences, 2023)
In these days modern English teacher should be aware of all useful techniques and methods of teaching English. While using such kind of methods, they may come across with many difficulties which students may get distracted during the lessons. Therefore, this article focuses on the methodological problems in teaching English to B1 level students using audio-visual authentic materials. Provided that several explanations to some teaching methods of foreign language by giving their positive and negative sides as well. Besides that, during the teaching process, EFL teachers may find using audio-visual authentic materials complicated due to the organizational issues. Taking account of foregoing, in this papers gives some tricky ways of applying audio-visual authentic materials in the classroom. So this paper attempted to investigate Uzbek teachers attitude towards the use of authentic materials at higher level in Uzbek schools according to communicative skills. Fifteen teachers who work at local schools were surveyed by the tool of questionnaire via google form for the purpose of this study. The results and feedbacks were provided at the end of the paper.